Breaking dawn - Meyer, Stephenie, 1973- (New York : Megan Tingley Books/Little, Brown and Co., 2012)
Although eighteen-year-old Bella joins the dark but seductive world of the immortals by marrying Edward the vampire, her connection to the powerful werewolf Jacob remains unsevered.
Awards: Winner of WHSmith Children's Book of the Year (part of Galaxy National Book Awards) 2009 (UK)
Originally published: New York : Little, Brown, 2008.
Keywords: Marriage -- Fiction; Paranormal fiction; Triangles (Interpersonal relations) -- Fiction; Vampires -- Fiction; Werewolves -- Fiction; Washington (State) -- Fiction; Fantasy fiction; Young adult fiction